Atypical antipsychotic initiation and the risk of type II diabetes in children and adolescents. (23rd March 2015) - Sohn, Minji; Talbert, Jeffery; Blumenschein, Karen; Moga, Daniela Claudia
Abstract Purpose To estimate the risk of type II diabetes (T2DM) in children and adolescents initiating atypical antipsychotic (AAP) therapy. Methods We conducted a retrospective cohort study using a new user design approach. Medical and pharmacy claims data between 1 January 2007 and 31 December 2009 for dependents ages 4 to 18 from an employed, commercially insured population from across the USA were included. AAP exposure was defined in the presence of a pharmacy claim preceded by at least six months of AAP‐free history. We used propensity score (PS) methodology to identify and match incident AAP users and non‐users. New‐onset T2DM, was defined based on medical and pharmacy claims. Follow‐up was extended until the date of new‐onset T2DM or the end of the study period. The risk of T2DM was evaluated in an intent to treat fashion using the Kaplan–Meier estimator and Cox proportional hazard regression that provided hazard ratio (HR) and associated 95% confidence interval (CI). Results Our study population included 6236 new AAP users and 22 080 non‐users. In this PS‐matched sample, the estimated risk of T2DM was twice as high in AAP users as non‐users (HR 2.18, 95% CI 1.45–3.29). Noticeable risk differences between AAP‐treated and control groups materialized within four months of AAP initiation and became constant after six months until the end of the follow‐up. Conclusions Children and adolescents who were prescribed an AAP medication had a two times higher risk of developing T2DM; our study raises questions about continued AAP use in children and adolescents. Copyright © 2015 John Wiley & Sons, Ltd.